Play as a child language: contemporary contributions - Maranhão, Joyce Hilario; Vieira, Camilla Araújo Lopes (Revista de Psicologia, 2017)
This theoretical study presents a bibliographical survey about the theoretical contributions of the freudo-lacanian psychoanalytic clinic regarding the psychic constitution and the function of playing as a modality of fantasy. The objective was to carry out a dialogue between the writings of Freud and Lacan with the ideas of contemporary psychoanalytic authors who have constructed a knowledge about the psychoanalytic clinic with children. Carried out the bibliographical survey of the works of the authors Ciaccia (2005), Flesher (2012), Kraemer and Betts (1989), Jerusalinsky (2004), Oliveira (2008), Santa-Roza (1993), Souza (1992). The study oriented activities with children’s in a non-governmental institution where play was one of the possible ways to listen to the they, discourse that is produced from the meaning of their experiences in the context of food deprivation and socioeconomic vulnerability. It is believed that the appropriation of psychoanalytic theory about play and its relation to the constitution of the subject can help in the construction of spaces that provide the playful capacity and the produce of creative narratives, so that the subject can express their fantasies and build social bond.